Investigating Dynamic Behavior and Control Systems of the F-16 Aircraft: Mathematical Modelling and Autopilot Design - Norouzi, Masoud; Caferov, Elbrus (International Sustainable Aviation Research Society, 2023)
The development of control systems for aerial vehicles necessitates a meticulous examination of their dynamic behavior. This research delves into an in-depth investigation of the dynamic behavior of the F-16 aircraft, employing refined mathematical models to analyze both its longitudinal and lateral motions, as well as their corresponding modes. These mathematical models are formulated in two conventional representations: state space equations and transfer functions. By utilizing these mathematical representations, two displacement autopilots have been developed, consisting of a pitch attitude autopilot based on the longitudinal equations and a roll attitude autopilot designed using the lateral equations. Proportional Integral Derivative (PID) controllers, encompassing inner loops, as well as Linear Quadratic Controllers (LQR), have been recruited as control system units. The control structures have undergone analysis utilizing Simulink models. The analyses have yielded favorable damping characteristics and faster responses in both longitudinal and lateral movements and modes.
Keywords: Aircraft Performance and Flight Control Systems; Flight Dynamics; Longitudinal Motion; Lateral Motion; Displacement Autopilots; LQR; PID; F-16 Aircraft; Uçak Performansı ve Uçuş Kontrol Sistemleri